THU0192 Combination therapy of leflunomide (lef) and methotrexate (mtx) is effective and well tolerated in rheumatoid arthritis (ra) patients inadequately responding to methotrexate (mtx) alone. (1st June 2001) - Kremer, JM; Genovese, M; Cannon, GW; Caldwell, JR; Cush, JJ; Luggen, ME; Furst, DE; Crawford, B; Bathon, J
Abstract : Background: Combination therapy for the treatment of patients with RA may improve response rate in those who have responded inadequately to MTX alone. As LEF is increasingly being used in RA management, it is relevant to determine the impact of adding LEF to MTX. Objectives: To investigate the benefits of adding LEF to an existing MTX regimen on efficacy, tolerability, physical function, and health-related quality of life (HRQOL) in patients with active RA in a 24-week multi-centre, randomised, double-blind placebo (PLC)-controlled trial. Methods: Subjects with active RA receiving MTX (15?20 mg/week) for > = 6 months and at a stable dose for > = 8 weeks were randomised to receive LEF 100 mg QD x 2 days followed by 10 mg QD thereafter (n = 130) or matching PLC (n = 133). Mean doses of MTX were 16.7 mg/week and 16.2 mg/week for LEF+MTX and PLC+MTX, respectively. The primary efficacy endpoint was ACR 20 responder rate at 24 weeks, with a secondary endpoint of ACR 20 response using LOCF, with both analysed in the ITT population. ACR 20, 50 and 70 response rates, as well as safety monitoring, were assessed every 2 weeks up to week 8, and every 4 weeks thereafter. The Health Assessment Questionnaire (HAQ) and Medical Outcomes Survey Short Form (SF-36) questionnaire were administered and the mean improvements from baseline were compared at week 24 for the LEF+MTX group and the PLC+MTX group. Results: Using the LOCF method, the ACR 20, 50 and 70 rates were LEF+MTX = 51.5%, 26.2% and 10.0% vs PLC+MTX = 23.3%, 6.0% and 2.3% (p < = 0.0001, p < = 0.0001, and p < = 0.02). At week 24, ACR 20 responder rates were LEF+MTX = 46.2% vs PLC+MTX = 19.5% (p < = 0.0001). Mean baseline values for the disability index (DI) derived from the HAQ were LEF+MTX = 1.6 vs PLC+MTX = 1.5 (NS). At 24 weeks, mean changes from baseline in HAQ DI were LEF+MTX = -0.42 vs PLC+MTX = -0.09 (p < = 0.0001); representing mean improvements of 29% and 5%, respectively, based on individual percent changes. Mean baseline values for the physical component summary scale (PCS) derived from the SF-36 were LEF+MTX = 28.4 vs PLC+MTX = 29 (NS). At 24 weeks, mean changes from baseline in the PC were LEF+MTX = 6.8 vs PLC+MTX = 0.3 (p < = 0.0001); representing mean improvements of 29% and 3%, respectively, based on individual percent changes. Reported AEs included diarrhoea (LEF+MTX = 25.4% vs PLC+MTX = 13.5%), upper respiratory infections (LEF+MTX = 22.3% vs PLC+MTX = 24.1%), nausea (LEF+MTX = 16.2% vs PLC+MTX = 11.3%) and dizziness (LEF = MTX = 7.7% vs PLC+MTX = 5.3%). Increases in LFTs of >3×ULN at any time during the 24-week treatment period for ALT and AST for LEF+MTX were 3.8% and 1.5%, respectively, compared to 0.8% on both for PLC+MTX. Conclusion: LEF combined with an existing MTX regimen in patients with active RA is well tolerated and confers significant therapeutic advantages in terms of both efficacy and quality of life.